Environmental concerns, knowledge and practices gap among Malaysian teachers - Mat Said, Aini; Ahmadun, Fakhru'l‐Razi; Hj. Paim, Laily; Masud, Jariah (Emerald, 2003)
Environmental problems are caused directly or indirectly by the patterns of production by industries, patterns of consumption and behavior of the consumers. The shaping of attitude and values, commitment and skills needed to preserve and protect the environment begins at an early age. Hence educators play an influential role in developing new patterns of behaviors for individuals. Accordingly, aims to determine the level of knowledge, environmental concern and ecologically conscious consumer behavior and identify the extent of involvement in nature‐related activities of school teachers. Also investigates the relationships between these variables. The subjects were 285 school teachers who were randomly selected from ten regular government schools in the state of Selangor, Malaysia. A survey was conducted using drop and collect method. The data illustrated the presence of high level of environmental concern among the teachers. The environmental knowledge was fair but generally poor in understanding of the underlying causes of environmental problems. The practices of environmentally responsible behavior were not in concert with the level of concern and knowledge. The respondents were not actively involved in nature‐related activities. Proposes ways of enhancing the ecological awareness and responsibilities of the teachers.